Hypovitaminosis-D and EBV: no interdependence between two MS risk factors in a healthy young UK autumn cohort. (May 2014) - Ramien, Caren; Pachnio, Annette; Sisay, Sofia; Begum, Jusnara; Leese, Alison; Disanto, Giulio; Kuhle, Jens; Giovannoni, Gavin; Rickinson, Alan; Ramagopalan, Sreeram V; Moss, Paul; Meier, Ute-Christiane
Late Epstein-Barr virus infection and hypovitaminosis-D as environmental risk factors in the pathogenesis of multiple sclerosis are gaining great interest. We, therefore, tested for in-vivo interdependence between Epstein-Barr-virus (EBV)-status and 25-hydroxyvitamin D3 (25(OH)D3) -level in healthy young individuals from a United Kingdom (UK) autumn cohort. EBV-load was measured by quantitative polymerase chain reaction and 25(OH)D3 levels by isotope-dilution liquid chromatography-tandem mass spectrometry. This young, healthy UK autumn cohort showed surprisingly low levels of 25(OH)D3 (mean value: 40.5 nmol/L ± 5.02). Furthermore, we found that low 25(OH)D3 levels did not impact on EBV load and anti-EBV nuclear antigen-1 (EBNA-1) titers. However, we observed a correlation between EBV load and EBNA-1 titers. These observations should be of value in the study of the potential relationship between hypovitaminosis-D and EBV-status in the pathophysiology of multiple sclerosis.